Nonfixation of the falciform ligament discovered during laparoscopic pyloromyotomy in a 3-week-old infant: A potential cause of intestinal obstruction - Caroline Maloney; Meade Barlow; Samuel Z. Soffer (Elsevier, 2016)
Failure of the peritoneum to fuse with the umbilical vein can lead to nonfixation of the falciform ligament. The exposed remnant of umbilical vein persists as a congenital band spanning the peritoneal cavity from the umbilicus to the liver. This abnormality has been associated with internal herniation and bowel obstruction in infants. We describe a case of pyloric stenosis in an infant who, at the time of laparoscopic pyloromyotomy, was found to have nonfixation of the falciform ligament causing a volvulus of the transverse colon without clinical signs of obstruction.